2023
DOI: 10.1038/s41421-022-00515-x
|View full text |Cite|
|
Sign up to set email alerts
|

Reprogramming of palmitic acid induced by dephosphorylation of ACOX1 promotes β-catenin palmitoylation to drive colorectal cancer progression

Abstract: Metabolic reprogramming is a hallmark of cancer. However, it is not well known how metabolism affects cancer progression. We identified that metabolic enzyme acyl-CoA oxidase 1 (ACOX1) suppresses colorectal cancer (CRC) progression by regulating palmitic acid (PA) reprogramming. ACOX1 is highly downregulated in CRC, which predicts poor clinical outcome in CRC patients. Functionally, ACOX1 depletion promotes CRC cell proliferation in vitro and colorectal tumorigenesis in mouse models, whereas ACOX1 overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…To explore the role of palmitoylation in STAT3 signaling, we treated cells with the palmitoylation inhibitor 2-Bromopalmitate (2-BP) [ 23 25 ] and the APT2 inhibitor ML349 [ 26 , 27 ]. 2-BP downregulated the level of STAT3 palmitoylation induced by LPS-PA, whereas ML349 upregulated it (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the role of palmitoylation in STAT3 signaling, we treated cells with the palmitoylation inhibitor 2-Bromopalmitate (2-BP) [ 23 25 ] and the APT2 inhibitor ML349 [ 26 , 27 ]. 2-BP downregulated the level of STAT3 palmitoylation induced by LPS-PA, whereas ML349 upregulated it (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The stability of ACOX1 is governed by DUSP14, which, through dephosphorylation, enhances ACOX1 degradation, thereby potentially accelerating CRC progression. This degradation leads to increased palmitoylation of β-linker proteins, furthering CRC advancement (Zhang et al 2023b ). CPT2, essential for fatty acid metabolism, is significantly downregulated in CRC, contributing to stem cell characteristics and oxaliplatin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, lipid metabolism is often modi ed, and studies have demonstrated that inhibiting lipid peroxidation can enhance CRC liver colonization in mouse models 12 . ACOX1, a key enzyme in fatty acid β-oxidation, acts as a tumor suppressor, and the downregulation of ACOX1 promotes CRC progression 13 . Carnitine palmitoyl transferase 1 (CPT1) controls the rate-limiting step of fatty acid oxidation (FAO).…”
Section: Introductionmentioning
confidence: 99%